Peran Media Sosial dalam Mendukung Inovasi dan Digitalisasi UMKM - Deddy Junaedi; Umi Masruro; Jannah; Riyan Laili; Alvyna Putri Rianita; Halimatut Tamimah (STKIP MAJENANG, 2023)
Social media plays an important role in supporting innovation and digitalization of Micro, Small and Medium Enterprises (MSMEs) in Indonesia. This research aims to understand how social media affects the growth of MSMEs through marketing strategies and interactions with consumers. The method used is qualitative analysis on several case studies of MSMEs that successfully use social media. The results show that social media increases product visibility and allows MSMEs to interact directly with customers, understand their neaeds, and adapt quickly to market trends. In addition, feedback from consumers on social media drives product and service innovation. The conclusion of this study is that social media not only improves the competitiveness of MSMEs, but also contributes to national economic growth. The suggestion for MSMEs is to utilize social media proactively and take part in digital marketing training.The implications of this study emphasize the need for support from the government and related institutions in the form of training programs and access to technology to strengthen the capabilities of MSMEs in the digital era. Thus, social media can be a strategic tool for sustainable growth and innovation in the MSME sector.